IoT honeypot: A review from researcher's perspective - Razali M.F.; Muruti G.; Razali M.N.; Jamil N.; Mansor F.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet of things; Malware; Security of data; Attack patterns; Deception toolkits; Honeypots; Malware attacks; Popular platform; Network security